Социологические аспекты мотивации финансового поведения населения - Леонов, В. (Социология: теория, методы, маркетинг, 2005)
The article is destined to reveal sociological characteristics of population’s financial behavior motivation. Motivating forces of monetary activity are presented in the form of incentive mechanism of socially determined behavior. They are aimed at the sociogenic needs satisfaction and are formed on the basis of group values, social attitudes and norms of specific community. Three kinds of financial behavior are distinguished: pragmatic efficiency motivation, institutional one, and intense emotions motivation.